CHARACTERIZATION OF MARCO-MEDIATED ENDOCYTOSIS - Tu, Zhongyuan (My University, 2012)
Class A scavenger receptors are multifunctional transmembrane glycoproteins that mediate macrophage functions like phagocytosis and endocytosis. The macrophage receptor with collagenous structure (MARCO) is one such receptor. It has been shown that the extracellular cysteine-rich domain of MARCO is responsible for ligand binding, but the role of the cytoplasmic domain in ligand uptake is unclear. The aim of the studies presented in this thesis is to characterize the role of the cytoplasmic domain of MARCO and to characterize the molecular pathway of MARCO-mediated endocytosis.
Full-length human MARCO (hMARCO) and Δ1-34hMARCO, which lacks the first thirty-four amino acids were created in order to determine whether amino acids 1-34 contained residues required for receptor internalization and surface expression. The constructs were stably expressed in HEK293T cells and found to have similar levels of surface expression and same rate of internalization without ligand. Interestingly, hMARCO, but not Δ1-34hMARCO, surface expression was up-regulated upon ligand incubation.
In order to ascertain the importance of clathrin, dynamin and actin in MARCO-mediated endocytosis, specific endocytic inhibitors were used. MARCO-mediated ligand uptake was inhibited when clathrin and actin polymerization and, dynamin functions were impaired by these inhibitors. Furthermore, ligand uptake by Δ1-34hMARCO-expressing HEK293T was insensitive to inhibitors of clthrin and dynamin but not inhibitors of actin.
In conclusion, MARCO mediates endocytosis via a clathrin-mediated, dynamin-dependent pathway that involves actin. Amino acids 1-34, are required clathrin and dynamin but not actin functions during MARCO-mediated endocytosis. Additionally, amino acids 1-34 might also be important for MARCO recycling but not receptor internalization or surface expression.
Keywords: endocytosis; scavenger receptors; MARCO; clathrin-mediated endocytosis; Biological Phenomena, Cell Phenomena, and Immunity; Biological Phenomena, Cell Phenomena, and Immunity